2001
DOI: 10.1046/j.1526-0968.2001.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Topics on Cryofiltration Technologies

Abstract: In the last 40 years, therapeutic plasmapheresis techniques have been improving considerably. These include cryofiltration technologies providing novel ways of removing large amounts of cryoproteins from plasma. The concept of cryofiltration involves exposure of plasma to below core (37°C) and room temperatures (25°C) without freezing. It was initially used to treat diseases such as cryoglobulinemia with systemic vasculitis, rheumatoid arthritis, systemic lupus erythematosus, and ABO-incompatible transplants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…These studies indicated that 14 IU/ml of sodium heparin is the lowest level of heparin required for application of the HCP method (data not shown). Heparin, a highly charged polyanion, is capable of forming soluble and insoluble complexes with proteins, which upon freezing and the application of centrifugal force will accelerate their precipitation [17,18] . The precipitate or the cryogel is insoluble in cold temperatures but mostly soluble at 37 ° C, enabling its removal by centrifugation at lower temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that 14 IU/ml of sodium heparin is the lowest level of heparin required for application of the HCP method (data not shown). Heparin, a highly charged polyanion, is capable of forming soluble and insoluble complexes with proteins, which upon freezing and the application of centrifugal force will accelerate their precipitation [17,18] . The precipitate or the cryogel is insoluble in cold temperatures but mostly soluble at 37 ° C, enabling its removal by centrifugation at lower temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is employed in selective removal of cryoglobulins and immunological complexes used in the treatment of cryoglobulinemia. Two types of cryofiltration are used: (1) removal of cryoglobulins precipitating in the temperature of 4 ° C and (2) removal of cryogel (anticoagulant complex consisting of fibrinogen, fibronectin, fibrin degradation products, cold insoluble proteins and heparin core) conducted in the temperature of 2-10 ° C [15,16] .…”
Section: New Options Of Apheresis In Renal Diseases: How?mentioning
confidence: 99%
“…This procedure selectively removes cryoproteins such as cryoglobulins to treat cryoglobulinemia and cryofibrinogen to treat cryofibrinogemia or any other cryoprotein to treat cryoprecipitate induced diseases [24,25]. In this procedure, plasma is separated, exposed to 48C in a thermoregulator unit, cryoprotein will be precipitated and removed by 4.3 micron pore size Cryofilter.…”
Section: Cryofiltration Apheresismentioning
confidence: 99%